2021
DOI: 10.3389/fnut.2021.719197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors of Licorice-Induced Pseudoaldosteronism Based on Glycyrrhizin-Metabolite Concentrations: A Narrative Review

Abstract: Licorice, the dried root or stolon of Glycyrrhiza glabra or G. ularensis, is commonly used worldwide as a food sweetener or crude drug. Its major ingredient is glycyrrhizin. Hypokalemia or pseudoaldosteronism (PsA) is one of the most frequent side effects of licorice intake. Glycyrrhizin metabolites inhibit type 2 11β-hydroxysteroid dehydrogenase (11βHSD2), which decomposes cortisol into inactive cortisone in the distal nephron, thereby inducing mineralocorticoid receptor activity. Among the several reported g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 58 publications
0
28
2
Order By: Relevance
“…Its metabolite, glycyrrhetic acid, facilitates potassium excretion and thus lowers total serum potassium. Attention should be paid to hypokalemia, myopathy, edema, and hypertension caused by pseudoaldosteronism [23]. The adverse event rate of pseudoaldosteronism in previous reports was 0.4% (four cases), while that in this study was 0.3% (three).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Its metabolite, glycyrrhetic acid, facilitates potassium excretion and thus lowers total serum potassium. Attention should be paid to hypokalemia, myopathy, edema, and hypertension caused by pseudoaldosteronism [23]. The adverse event rate of pseudoaldosteronism in previous reports was 0.4% (four cases), while that in this study was 0.3% (three).…”
Section: Discussioncontrasting
confidence: 62%
“…Homma suggested that 60 years of age and older, administration for more than 30 days, and concomitant use of drugs inducing hypokalemia were risk factors for developing pseudoaldosteronism [25]. Mantani speculated that the incidence in patients administered Glycyrrhiza 1 g/day was 1.0%, that with 2 g/day 1.7%, that with 4 g/day 3.3%, and that with 6 g/day 11.1% [23]. In this study, it occurred in elderly patients ranging from 69 to 92 years old who were administered Glycyrrhiza 1.5 g/day for 3–8 days.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there was no significant change of ECW/TBW or potassium level in the whole cohort (Table 2). The dose dependency of glycyrrhiza‐induced pseudo‐aldosteronism has been reported [31]. However, the contained amount of glycyrrhiza is only 1.0 g in 7.5 g rikkunshito.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizic acid is the primary source of sweetness in licorice, but it is metabolized to glycyrrhetinic acid, which inhibits type-2 11β-hydroxysteroid dehydrogenase (Molhuysen et al, 1950). 11β-Hydroxysteroid dehydrogenase decomposes cortisol in the distal nephron, and inhibition of this enzyme can cause hypokalemia and have other effects related to mineralocorticoid receptor activity (Yoshino et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the United States Food and Drug Administration (FDA) has established guidance for clinical evaluation of drug-drug pharmacokinetic interactions involving CYP enzymes (U.S. Food and Drug Administration, 2020), and similar clinical studies have been described for the evaluation of the drug-botanical pharmacokinetic interactions (Yoshino et al, 2021). The approach involves measuring the effect of the test drug or botanical dietary supplement on the pharmacokinetics of a low dose of a probe drug or a cocktail of probe drugs, each of which is metabolized by a specific CYP enzyme.…”
Section: Introductionmentioning
confidence: 99%